Comparing the performance of sway control using ZV input shaper and LQR on gantry cranes - Alhassan, Ahmad (2015)
This paper presents the investigation into the performance of ZV input shaper and LQR for sway control of a non linear gantry crane systems. The non linear model of the system was derived using the Lagrangian energy equation and then linearized using Taylor's series expansion. ZV input shaper was proposed using the estimated natural frequency and damping ratio of the system. LQR was also designed by selecting appropriate performance index to the system. Performances of the controllers are assesses based on time response specifications and level of oscillation reduction. MATLAB simulation results of the system subjected to a pulse input torque shows that LQR was more effective and reliable